A terminally protected dipeptide: from crystal structure and self-assembly, through co-assembly with carbon-based materials, to a ternary catalyst for reduction chemistry in water. Issue 1 (14th October 2015) - Mazzier, Daniela; Carraro, Francesco; Crisma, Marco; Rancan, Marzio; Toniolo, Claudio; Moretto, Alessandro
Abstract : An efficient catalyst for reduction chemistry in water was prepared by the co-assembly of a hydrophobic dipeptide, multiwalled carbon nanotubes, and C60 . Abstract : A terminally protected, hydrophobic dipeptide Boc-l -Cys(Me)-l -Leu-OMe (1 ) was synthesized and its 3D-structure was determined by single crystal X-ray diffraction analysis. This peptide is able to hierarchically self-assemble in a variety of superstructures, including hollow rods, ranging from the nano- to the macroscale, and organogels. In addition, 1 is able to drive fullerene (C60 ) or multiwalled carbon nanotubes (MWCNTs) in an organogel by co-assembling with them. A hybrid1 -C60 –MWCNT organogel was prepared and converted (through a high vacuum-drying process) into a robust, high-volume, water insoluble, solid material where C60 is well dispersed over the entire superstructure. This ternary material was successfully tested as a catalyst for: (i) the reduction reaction of water-soluble azo compounds mediated by NaBH4 and UV-light with an overall performance remarkably better than that provided by C60 alone, and (ii) the NaBH4 -mediated reduction of benzoic acid to benzyl alcohol. Our results suggest that the self-assembly properties of1 might be related to the occurrence in its single crystal structure of a sixfold screw axis, a feature shared by most of the linear peptides known so far to give rise to nanotubes.